Imaging bacterial infection with 99mTc-ciprofloxacin (Infecton). Issue 11 (1st November 2002) - Britton, K E; Wareham, D W; Das, S S; Solanki, K K; Amaral, H; Bhatnagar, A; Katamihardja, A H S; Malamitsi, J; Moustafa, H M; Soroa, V E; Sundram, F X; Padhy, A K
Abstract : Aims: The diagnosis of deep seated bacterial infections, such as intra-abdominal abscesses, endocarditis, and osteomyelitis, can be difficult and delayed, thereby compromising effective treatment. This study assessed the efficacy of a new radioimaging agent, Tc-99m ciprofloxacin (Infecton), in accurately detecting sites of bacterial infection. Methods: Eight hundred and seventy nine patients with suspected bacterial infection underwent Infecton imaging and microbiological evaluation. The sensitivity and specificity of Infecton in detecting sites of bacterial infection were determined with respect to Centres of Disease Control, World Health Organisation, and Dukes's criteria. Results: Five hundred and seventy four positive and 295 negative images were produced. These included 528 true positives, 46 false positives, 205 true negatives and 90 false negatives, giving an overall sensitivity of 85.4% and a specificity of 81.7% for detecting infective foci. Sensitivity was higher (87.6%) in microbiologically confirmed infections. Conclusions: Infecton is a sensitive technique, which aids in the earlier detection and treatment of a wide variety of deep seated bacterial infections. The ability to localise infective foci accurately is also important for surgical intervention, such as drainage of abscesses. In addition, serial imaging with Infecton might be useful in monitoring clinical response and optimising the duration of antimicrobial treatment.